Identification, validity, and reliability of the 21st-century workplace skills for on-the-job training practicum - P. Miranda, John Paul; B. Dianelo, Roque Francis; B. Gamboa, Almer; Bansil, Joseph Alexander; R. Regala, Agnes; S. Simpao, Laharni (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study aimed to develop and evaluate an instrument for measuring 21st-century workplace skills in on-the-job training (OJT) trainees. A literature review identified 20 key skills, which became the foundation of the instrument. Its validity and reliability were tested through a pilot study involving 20 OJT supervisors, employing methods like the item-level content validity index (I-CVI) and Cronbach’s alpha. The results confirmed the instrument’s effectiveness, indicating the need for further research with larger and more diverse samples to enhance its applicability. This tool is crucial in improving OJT programs by enabling supervisors to assess and support trainees more effectively. Additionally, it serves as a resource for employers and educators in appraising potential hires and graduates, and assists institutions in refining their curricula.